A Microeconometric Analysis of Spillovers within the Canadian Wage Determination Process - Christofides, Louis N.; Swidinsky, Robert; Wilton, David A. (The Review of Economics and Statistics, 1980)
Louis N. Christofides, Robert Swidinsky, David A. Wilton, A Microeconometric Analysis of Spillovers within the Canadian Wage Determination Process, The Review of Economics and Statistics, Vol. 62, No. 2 (May, 1980), pp. 213-221